IMPLEMENTING INTERCULTURE TO IMPROVE SELF-CONFIDENCE OF CHILDREN WITH SPECIAL NEEDS - Nur Mahardika; Sekar Dwi Ardianti; Savitri Wanabuliandari; Mahardika Supratiwi; Priyono Priyono (Program Studi PGSD Universitas Flores, 2026)
Observations in several Inclusive Elementary Schools in Kudus Regency show that students with special needs still experience significant challenges in participating in the learning process. The urgency of this research lies in the need to improve the self-confidence of students with special needs. This study aims to assess the effectiveness of the Interactive Educational Game Media Based on Ethnic Culture (INTERCULTURE) in enhancing the self-confidence of students with special needs. The research method employed is quantitative, with a Pre-Experimental One-Group Pretest–Posttest Design. In this design, students are given a pretest to assess their self-confidence, followed by treatment through INTERCULTURE media-based learning activities, and then a posttest to determine whether there is a significant change after the intervention. Data collection was conducted using test instruments to assess students’ self-confidence. Data analysis was conducted using the Paired Sample t-Test and the N-Gain Test. The results of this analysis indicate a significant improvement in the self-confidence of students with special needs after using the INTERCULTURE media.